Gender wage and productivity gaps in the Ethiopian manufacturing sector - Melaku Abegaz; Gibson Nene (Journal of Applied Economics, 2023)
The paper uses firm-level data to examine gender wage and productivity gaps in the Ethiopian manufacturing sector for the period 1996-2010. It investigates gender wage differentials between skilled and unskilled workers after controlling for factors affecting average wages. Our findings show significant gender wage and productivity gaps and the segregation of female workers into low-paying firms. Controlling for average productivity reduces the magnitude of the wage gap but does not eliminate it. However, results using a simultaneaous estimation of wage equation and production function at a firm-level indicate no significant difference between the gender wage and productivity gaps. As such, further investigation into the sources of the dual gaps using matched employer-employee data is necessary. The Ethiopian government should focus on skill development to improve the productivity of female workers and address the segregation of female workers into low-paying firms.
Keywords: 330; Ethiopia; gender productivity gap; gender wage gap; globalization; manufacturing; sub-Saharan Africa